Optimizing the Role of Regional House of Representatives in the Supervision Function of Regional Development (Case Study in Semarang City of Regional House of Representatives) - Ilma Maulana Fitra Islamy; Pulung Brahmantyo; Muhammad Iqbal Baiquni (Universitas Muhammadiyah Tangerang, 2022)
Based on Law no. 23 of 2014 in Article 42 paragraph 1 C provides a mandate that the Regional House of Representatives (DPRD) supervises Regional Regulations, Regional Head Decrees, Regional Government policy packages, and the implementation of APBD in regional development plans, as well as international cooperation in the regions in the context of actualization. DPRD function. The function of the DPRD is very vital in evaluating the implementation of development in the region by supervising each stage starting from the planning stage, the ratification stage, the implementation stage, to the accountability stage by the Regional Government. In addition, the supervisory function of the DPRD can minimize fraudulent actions by the Regional Government to avoid being hampered or stalled by regional development. empirical juridical method, which is an approach that examines secondary data first and then continues by conducting primary data research in the field. The results of this study are the implementation of the supervisory function is very important, the DPRD must optimize its supervisory function by minimizing obstacles such as technical constraints, constraints on the interests of the parties, infrastructure constraints, and even the lack of community participation in order to create a good supervisory function for the sake of support regional development.